Procyanidin B2 Protects Neurons from Oxidative, Nitrosative, and Excitotoxic Stress - Taylor C. Sutcliffe; Aimee N. Winter; Noelle C. Punessen; Daniel A. Linseman (MDPI AG, 2017)
The aberrant generation of oxygen and nitrogen free radicals can cause severe damage to key cellular components, resulting in cell apoptosis. Similarly, excitotoxicity leads to protease activation and mitochondrial dysfunction, which subsequently causes cell death. Each of these factors play critical roles in the neuronal cell death underlying various neurodegenerative diseases. Procyanidin B2 (PB2) is a naturally occurring polyphenolic compound found in high concentrations in cocoa, apples, and grapes. Here, we examine the neuroprotective effects of PB2 in primary cultures of rat cerebellar granule neurons (CGNs) exposed to various stressors. CGNs were pre-incubated with PB2 and then neuronal stress was induced as described below. Mitochondrial oxidative stress was triggered with HA14-1, an inhibitor of the pro-survival Bcl-2 protein which induces glutathione-sensitive apoptosis. Glutamate and glycine were used to induce excitotoxicity. Sodium nitroprusside, a nitric oxide generating compound, was used to induce nitrosative stress. We observed significant dose-dependent protection of CGNs with PB2 for all of the above insults, with the greatest neuroprotective effect being observed under conditions of nitrosative stress. Intriguingly, the neuroprotective effect of PB2 against nitric oxide was superoxide-dependent, as we have recently shown for other catechol antioxidants. Finally, we induced neuronal stress through the removal of depolarizing extracellular potassium and serum (5K conditions), which is a classical model of intrinsic apoptosis in CGNs. PB2 did not display any significant protection against 5K-induced apoptosis at any concentration tested. We conclude that PB2 offers neuronal protection principally as an antioxidant by scavenging reactive oxygen and nitrogen species instead of through modulation of pro-survival cell signaling pathways. These findings suggest that PB2 may be an effective neuroprotective agent for the treatment of neurodegenerative disorders.